ERK1/2 MAPKs and Wnt Signaling Pathways are Independently Involved in Adipocytokine-Mediated Aldosterone Secretion - Vleugels, K.; Schinner, S.; Krause, D.; Morawietz, H.; Bornstein, S. R.; Ehrhart-Bornstein, M.; Krug, A. W. (Experimental and Clinical Endocrinology & Diabetes, 2011)
Obesity is one major risk factor for the development of arterial hypertension, and the development of obesity-related hypertension has been associated with increased plasma aldosterone levels. Our previous work shows a direct stimulatory effect of adipokines on aldosterone secretion from human adrenocortical cells, mediated via ERK1/2-dependent upregulation of steroid acute regulatory protein (StAR) activity. Recent evidence also indicates the involvement of the Wnt-signaling pathway in fat cell-mediated aldosterone secretion. Wnt-signaling molecules are secreted by adipocytes and regulate the activity of SF-1, a key transcription factor in adrenal steroidogenesis. The goal of this study was to investigate the cellular mechanisms of adipocyte-induced aldosterone secretion in detail, and to evaluate effects and possible interactions of the ERK1/2 MAPK- and the Wnt-signaling pathways on adipocyte-induced adrenocortical aldosterone secretion. Our results show that, similar to adipocyte-conditioned medium (ACM), β-catenin, which is an intracellular mediator of canonical Wnt-signaling, induced StAR promotor activity in human NCI-H295R adrenocortical cells, and ACM-induced StAR promotor activity depended on intact SF-1 binding sites. Wnt antagonist sFRP-1 inhibited adipokine-mediated StAR activity, but did not affect ERK1/2 MAPK activation. Accordingly, Wnt did not stimulate ERK1/2 phosphorylation in adrenocortical cells, indicating that ERK1/2 MAPK and Wnt signaling pathways are independently involved in adipocyte-mediated aldosterone secretion.
Keywords: obesity; adipocytokines; hypertension; aldosterone; adrenal cortex; ERK1/2 MAPK; Wnt